Incorporating Collaborative Learning in an English Course Using Whatsapp - Syah, Muhammad Noor Sulaiman (Journal of English Teaching and Learning Issues, 2020)
In this era of globalization which consists of technological generation, a mobile phone is needed in the teaching and learning process. Students make their mobile phones an inseparable part of themselves. WhatsApp, is the most favored mobile based applications among students, will be the potential application for incorporating collaborative learning. Therefore, this study aims to explore the incorporation of collaborative learning in an English course using WhatsApp and to identify the students’ perception toward that tool in an English course. This case study was conducted in the Arabic Education department of IAIN Kudus, on second semester students of 2019/2020. Two different sources of data were used to collect the information needed for answering the research questions. They were analysis of participants’ posts on the WhatsApp group platform and survey questionnaire using Likert scale. The process of teaching learning activities, including four language skills, in English course through the participants’ posts on the WhatsApp group platform are presented. The quantitative data from the response of Likert scale questionnaires is also analyzed qualitatively. Overall, the study shows that WhatsApp is a convenient tool for incorporating collaborative learning in English course and students get positive feelings and intentions regarding the potential use of WhatsApp in their learning.